Effect of heat treatment of wild cherry wood on abrasion resistance and withdrawal capacity of screws - Aytin, Ayhan; Korkut, Süleyman; As, Nusret; Uysal, Öner; Gündüz, Gökhan (Drvna Industrija, 2015)
In its wise use, many properties of wood are important. Among these properties, wood abrasion resistance (AR) and withdrawal capacity of screws (WCS) are deemed to be relatively signifi cant. It is well know that heat treatment changes the resistance features of wooden materials by changing the structural characteristics of wood. Within the scope of this study, the effects were investigated of the temperature and duration of heat treatment of Wild Cherry (Cerasus avium (L.) Monench) on its AR and its WCS in the radial direction and tangential direction. The test results indicated that weight loss (WL) and thickness reduction (TR) remained almost the same in the radial direction specimen, but there was signifi cant TR in the tangential direction specimen. As a result of these changes, the abrasion effect of the S-42 abrader diminished based on the increase in the number of cycles. However, in both the radial and tangential direction, the WCS decreased to a signifi cantly greater extent in the heat-treated specimens than in the control specimens
Keywords: Heat treatment; Thermowood; Abrasion resistance; Withdrawal capacity of screws; Wild cherry wood; Ağaç; Orman endüstrisi; Ormancılık; Forestry